Transformasi Standar Nasional dan Akreditasi Pendidikan Tinggi - Ayu Miranda Limbong; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2024)
- The aim of this study is to realize the vision of an advanced Indonesia that is sovereign, independent and has personality through the creation of Pancasila students. The Ministry of Education, Culture, research and technology continues to advance in presenting various breakthroughs. Freedom to learn. Freedom to learn, which is promoted by the Ministry of Education and Culture, Research and Technology, also has the aim of achieving quality education for all Indonesian people. In this report, this study uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from the Ministry of Education and Culture's YouTube channel entitled "Transformation of National Standards and Accreditation of Higher Education" which was presented by the Minister of Education, Culture, Research and Technology, the results of this study. explained that the transformation of national standards and higher education accreditation provides freedom or liberates universities in various aspects, where these universities can determine dirsection and policies while still referring to the quality standards that have been set. Providing wider space for universities to innovate and developthe potential that exists in higher education in optimizing the Tri Dharma activities of national higher education and higher education accreditation is a framework so that it will provide more flexibility for higher education institutions to be more adaptive and responsive to the demands of stakeholders. very dynamic interests. This will provide more energy for universities to continue to innovate in order to improve the quality of research education and community service in a sustainable manner.